Ammonium Adsorption by Geopolymer from Thach That Laterite - Thi Hoai, Ta; Thi Hong Hanh, Nguyen; Thi Hai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study aims to assess the ammonium (NH 4 + ) removal ability of geopolymer made from laterite. The results showed that the NH 4 + adsorption efficiency of laterite-based geopolymer (GL) was 9 times higher than raw laterite (LR). GL demonstrated a rapid increase in NH 4 + adsorption efficiency in the first 30 minutes, followed by a 90-minute gradual increase and stabilization. The NH 4 + adsorption isotherm of GL well fitted with both Langmuir and Freundlich models with a maximum adsorption capacity of 5.28 mg/g. The adsorbent dosage has influenced the adsorption capacity of GL, with the optimal ratio of adsorbent and solution volume being 10g/L. The SEM morphology structure of LR and GL indicates an increase in the surface area owing to higher regions of rough structures in GL compared to LR, contributing to the increment of NH 4 + adsorption capacity. These findings emphasize the potential of ammonium removal of laterite-based geopolymer in an aqueous environment.